Earthquakes that Uplifted Cyprus in the last 4 ka - Yildirim, Cengiz; Melnick, Daniel; Tüysüz, Okan; Altınbaş, Cevza Damla; Jara-Munoz, Julius; Tsanakas, Konstantinos; Özcan, Orkan; Strecker, Manfred (Copernicus GmbH, 2022)
Cyprus is located right on the plate boundary where the African Plate subducts beneath the Anatolian Microplate. Although subduction zones are earthquake-prone areas, the seismicity of the Cyprus and adjacent areas are not very active during the instrumental period. Nevertheless, archaeological and historical data indicate casualties and destructions within the island because of strong tremors and tsunamigenic waves. None of these data gives information about the source faults of these earthquakes. Are they far-field earthquakes (e.g., AD 365 Crete) or near-field earthquakes that occurred nearshore of the island? We focused on the island’s coast and mapped geomorphological, sedimentological, biological, and archaeological strain markers to answer these questions. Our geomorphological observations reveal the presence of at least three major Holocene abrasion platform levels uplifted coseismically. The presence of biological markers such as reef rims provides a dateable material to quantify these events. We also observed archaeological fish tanks as evidence of coseismic uplift of the shoreline during the historical periods. Radiocarbon 14C dating results indicate a temporal clustering of earthquakes within the 1300-1700 yr BP, 2000-2200 yr BP, and 4500 yr BP, which indicate overlapping of 4th and 6th-century historical earthquakes and also older earthquakes beyond the historical records.